2021
DOI: 10.1111/are.15207
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of microorganisms potentially beneficial for intensive cultivation of Penaeus vannamei under biofloc conditions: Highlighting Exiguobacterium acetylicum

Abstract: The aim of this work was to isolate, identify and characterize microorganisms present in intensive nursery of Penaeus vannamei during the spontaneous generation of the biofloc and to verify among the isolates, beneficial strains for the intensive cultivation of shrimp under biofloc conditions. 91 strains were isolated and identified by molecular taxonomy. Then, the strains were analysed for the presence of the aiiA gene responsible for the inherited transmission for the production of lactonase.Only Exiguobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Scarce are the environments on Earth not colonized by bacteria. In addition to naturally playing important roles from driving biogeochemical cycles at the ecosystem level ( Cavicchioli et al, 2019 ; Arrigo, 2005 ; Falkowski et al, 2008 ) to supporting host health at the individual level ( Berendsen et al, 2012 ; Manor et al, 2020 ; Gilbert et al, 2018 ), bacteria have also been harnessed for countless biotechnological applications across industries such as food preservation ( Motarjemi, 2002 ), plant and animal health ( Berendsen et al, 2012 ; Júnior et al, 2021 ), biocontrol of pathogens ( Köhl et al, 2019 ), as well as decomposition of toxic compounds, and production of valuable ones ( Varjani et al, 2017 ; Ro et al, 2006 ; Fang and Smith, 2016 ; Mainka et al, 2021 ). In natural environments, bacteria often form rich and complex communities, but understanding how these communities organize has proven difficult ( Widder et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scarce are the environments on Earth not colonized by bacteria. In addition to naturally playing important roles from driving biogeochemical cycles at the ecosystem level ( Cavicchioli et al, 2019 ; Arrigo, 2005 ; Falkowski et al, 2008 ) to supporting host health at the individual level ( Berendsen et al, 2012 ; Manor et al, 2020 ; Gilbert et al, 2018 ), bacteria have also been harnessed for countless biotechnological applications across industries such as food preservation ( Motarjemi, 2002 ), plant and animal health ( Berendsen et al, 2012 ; Júnior et al, 2021 ), biocontrol of pathogens ( Köhl et al, 2019 ), as well as decomposition of toxic compounds, and production of valuable ones ( Varjani et al, 2017 ; Ro et al, 2006 ; Fang and Smith, 2016 ; Mainka et al, 2021 ). In natural environments, bacteria often form rich and complex communities, but understanding how these communities organize has proven difficult ( Widder et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the leading genera revealed in this study's healthy state, namely Acinetobacter and Candidatus Bacilloplasma, were reported to act as a central hub connecting the significant bacterial population in the network of healthy shrimp hepatopancreas [ 51 ]. Further, Exiguobacterium genera in the healthy state have improved growth and survival in P. vannamei and provided probiotic advantages [ 7 , 11 ]. Lactobacillus members identified in this study are known probiotics and have been extensively studied for their abilities to maintain animal health [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, due to their ability to utilize many organic substrates, microorganisms have been used to maintain water quality, particularly by the autotroph nitrifying bacteria. In addition, their role in controlling pathogens in disease management and minimizing environmental impacts in the system has also been widely documented (de Mello Júnior et al, 2021; Martínez‐Córdova et al, 2017; Ortiz‐Estrada et al, 2020).…”
Section: Use Of Microorganisms In Aquaculturementioning
confidence: 99%